2022
DOI: 10.1177/11786388221107801
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet of Pregnant Women in Central South Africa: The NuEMI Study

Abstract: Introduction: The Mediterranean diet (MeD) has been shown to have significant health benefits for adults and children. A mother’s diet during pregnancy directly impacts the health of her offspring. This study aimed to investigate the adherence to the MeD of pregnant women attending antenatal care at a Regional Hospital in Bloemfontein, South Africa (SA). Methods: A cross-sectional study was conducted on a consecutive sample of 681 pregnant women who attended the antenatal clinic of a Regional Hospital in Bloem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In accordance with our results, an older maternal age, advanced education level, and greater social status were related with elevated compliance with the MD pre-pregnancy, whereas an unhealthy lifestyle like smoking and a low frequency of exercise were related with reduced compliance with the MD [ 49 ]. A cross-sectional study conducted on 681 pregnant women also indicated that higher compliance with the MD was related with an advanced education level and better annual income [ 50 ]. Another study also reported that greater compliance with the MD was related to a better socioeconomical level and more frequent physical activity, while greater compliance with the MD was further related with living in an urban region [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, an older maternal age, advanced education level, and greater social status were related with elevated compliance with the MD pre-pregnancy, whereas an unhealthy lifestyle like smoking and a low frequency of exercise were related with reduced compliance with the MD [ 49 ]. A cross-sectional study conducted on 681 pregnant women also indicated that higher compliance with the MD was related with an advanced education level and better annual income [ 50 ]. Another study also reported that greater compliance with the MD was related to a better socioeconomical level and more frequent physical activity, while greater compliance with the MD was further related with living in an urban region [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a higher maternal BMI is associated with reduced Bifidobacterium in breastmilk ( 46 ), which might suggest that South African mothers, who had higher mean weight, had less Bifidobacterium in their breastmilk than Nigerian mothers, leading to less Bifidobacterium in their infants’ gut. An additional explanation is that Nigerian mothers in this setting have a diet rich in fermented foods, whereas South African mothers may have a more Westernized diet ( 47 , 48 ). South African infants also had higher relative abundance of B. longum but lower relative abundance of B. infantis at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a higher maternal BMI is associated with reduced Bifidobacterium in breastmilk [ 48 ], which might suggest that South African mothers, who had higher mean weight, had less Bifidobacterium in their breastmilk than Nigerian mothers, leading to less Bifidobacterium in their infants’ gut. An additional explanation is that Nigerian mothers in this setting have a diet rich in fermented foods, whereas South African mothers may have a more Westernised diet [ 49 , 50 ]. South African infants also had higher relative abundance of B. longum but lower relative abundance of B. infantis at baseline.…”
Section: Discussionmentioning
confidence: 99%